Myaesthenia gravis exacerbation caused by axillary injection of botulinum toxin A for treatment of hyperhidrosis. (23rd January 2017) - El‐Heis, S.; Burke, G.; Gibb, W.; Ardern‐Jones, M. R.
Abstract : Clickhere for the corresponding questions to this CME article.